Economic Geology: Then and Now - Jébrak, Michael (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2006)
SUMMARY The science of mineral deposits (economic geology) has greatly evolved since its inception in the late 19th century, and has subsequently been strongly influenced by mining discoveries. It is a science that has moved from a descriptive phase to a deeper understanding of ore-body genesis. As a result, deposit types are increasing in number, classification systems are improving, and we are beginning to recognize how spatial and temporal distributions relate to plate tectonic mechanisms. Our understanding of ore-forming mechanisms has broadened, thanks, in part, to widely available isotopic dating methods and to advances in analytical techniques that determine the ore-element sources, transport conditions and depositional processes. It also appears that the climate and fundamental geodynamic processes (i.e. mantle plumes) play important roles in ore-deposit formation.